Home Confinement in Previously Active Older Adults: A Cross-Sectional Analysis of Physical Fitness and Physical Activity Behavior and Their Relationship With Depressive Symptoms - Carvalho, Joana; Borges-Machado, Flávia; Pizarro, Andreia N.; Bohn, Lucimere; Barros, Duarte (Frontiers in Psychology, 2021)
Abstract Aim: To analyze physical activity levels, sitting time, physical fitness, and their relationship with depressive symptoms after home confinement in previously active older adults. Methods: This cross-sectional study sample comprised 68 older adults (74.24 ± 5.67 years) from a community-based exercise program conducted in Porto, Portugal. After home confinement, participants were assessed in-person for lower-body strength (30-second chair stand test), cardiorespiratory fitness (6-minute walking test), agility/dynamic balance (8-foot up-and-go test), handgrip strength, and anthropometry. Telephone interviews were performed to evaluate depressive symptoms with the Geriatric Depression Scale – 15 items (GDS-15) and physical activity levels through the International Physical Activity Questionnaire (IPAQ-SV). Individuals were also asked to self-report changes in their physical activity levels and time spent sitting. Results: 90% of older adults self-reported a decrease in overall physical activity levels and nearly 65% increased daily sitting time during the home confinement. However, previously active older adults still presented high levels of physical fitness (scores above 50th compared to Portuguese normative values) after 11 weeks of home confinement. Overall, 52.9% of participants scored 5 or more points on GDS-15, which is suggestive of depression. Higher levels of moderate-to-vigorous physical activity (MVPA) and cardiorespiratory fitness were found in the non-depressed group compared to the depressed group. Finally, results from multiple regression analysis revealed that MVPA was negatively associated with depression. This model explained 16.4% of the variability seen in depression score, controlled for age, gender and education. Conclusion: Even reporting a decline in physical activity, older adults who previously participated in formal exercise program, still presented high levels of physical fitness after 11 weeks of home confinement. However, MVPA but not physical fitness seems to be associated depression score in previously active older adults. These results reinforce the importance of older adults to remain physically active, since higher levels of MVPA may have a protective effect on depressive symptoms and therefore, mitigate the negative impact of home confinement on mental health. Future longitudinal research studies are needed to ascertain these results.